2009
DOI: 10.1088/0960-1317/19/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

Geometric improvement of electrochemical discharge micro-drilling using an ultrasonic-vibrated electrolyte

Abstract: Electrochemical discharge machining (ECDM) is a spark-based micromachining method especially suitable for the fabrication of various microstructures on nonconductive materials, such as glass and some engineering ceramics. However, since the spark discharge frequency is drastically reduced as the machining depth increases ECDM microhole drilling has confronted difficulty in achieving uniform geometry for machined holes. One of the primary reasons for this is the difficulty of sustaining an adequate electrolyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…Vibration and magnetic field can be applied in combined hybrid processes to improve the performance of these processes. An ultrasonic-vibrated electrolyte in micro-ECDM enhances the machining depth by assuring an adequate flow of electrolyte for spark generation and chip removal in the gap between the tool and the workpiece [163]. Moreover, it is shown that the magneto-hydrodynamic convection induced by the magnetic field can effectively enhance electrolyte circulation, which contributes to higher machining performance.…”
Section: Combined and Assisted Hybrid Processesmentioning
confidence: 99%
“…Vibration and magnetic field can be applied in combined hybrid processes to improve the performance of these processes. An ultrasonic-vibrated electrolyte in micro-ECDM enhances the machining depth by assuring an adequate flow of electrolyte for spark generation and chip removal in the gap between the tool and the workpiece [163]. Moreover, it is shown that the magneto-hydrodynamic convection induced by the magnetic field can effectively enhance electrolyte circulation, which contributes to higher machining performance.…”
Section: Combined and Assisted Hybrid Processesmentioning
confidence: 99%
“…The following strategies were explored so far: optimizing the tool-electrode shape, promotion of the electrolyte flow by tool-electrode motions (e.g., tool vibrations [51][52][53][54] and tool rotation [48,52,55,56]), electrolyte motion [57] and flushing of the micro-hole in function of the measured force exerted on the toolelectrode [53,58]. • Optimizing heat transferred to the work-piece: Controlling the heat generated can be achieved passively or actively.…”
Section: Control Strategies For Sacementioning
confidence: 99%
“…This is achieved either by using small machining voltages [18] or by reducing the time during which the voltage is applied [58,60,63,64]. Another promising approach is to control the discharge location by using side insulated tool-electrodes [57,65].…”
Section: Control Strategies For Sacementioning
confidence: 99%
“…A host of literature proved that electrolyte circulation plays an important role in machining performance. Many approaches to enhancing the electrolyte circulation in ECDM and wire ECDM have been proposed [23][24][25]. Fang used rotary helical electrodes in wire ECDM, which accelerated the cycle of the electrolyte [26].…”
Section: Introductionmentioning
confidence: 99%